2017
DOI: 10.1515/sggw-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deforestation on water chemistry in the Kościeliska Valley in the Western Tatras in southern Poland

Abstract: Effect of deforestation on water chemistry in the Kościeliska Valley in the Western Tatras in southern Poland. Bark beetle infestation is a leading source of local tree stand damage in Tatra National Park. In addition, hurricane-force winds also cause damage to tree stands, as in the case of the 2013 wind event in the Kopki Kościeliskie area of the Kościeliska Valley. The purpose of the study was to determine the effect of deforestation on seasonal changes in water chemistry, especially in the case of nitrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…While our sulphate data align with these findings, the increase in nitrate levels in our study suggests other influencing factors, as long-term trends indicate decreasing nitrate levels in the Tatra Mountains (Kopáček et al, 2019 ). In our study area, a key factor contributing to increased nitrate levels could be deforestation, particularly after wind events and bark beetle infestations, as documented by Želazný et al ( 2017 ). They found that nitrate concentrations in stream water increased significantly, especially outside the vegetation season.…”
Section: Discussionmentioning
confidence: 74%
“…While our sulphate data align with these findings, the increase in nitrate levels in our study suggests other influencing factors, as long-term trends indicate decreasing nitrate levels in the Tatra Mountains (Kopáček et al, 2019 ). In our study area, a key factor contributing to increased nitrate levels could be deforestation, particularly after wind events and bark beetle infestations, as documented by Želazný et al ( 2017 ). They found that nitrate concentrations in stream water increased significantly, especially outside the vegetation season.…”
Section: Discussionmentioning
confidence: 74%